2020
DOI: 10.4049/jimmunol.1900959
|View full text |Cite
|
Sign up to set email alerts
|

ARID1a Associates with Lymphoid-Restricted Transcription Factors and Has an Essential Role in T Cell Development

Abstract: Maturation of lymphoid cells is controlled by the action of stage and lineage-restricted transcription factors working in concert with the general transcription and chromatin remodeling machinery to regulate gene expression. To better understand this functional interplay, we used Biotin Identification in human embryonic kidney cells to identify proximity interaction partners for GATA3, TCF7 (TCF1), SPI1, HLF, IKZF1, PAX5, ID1, and ID2. The proximity interaction partners shared among the lineagerestricted trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 88 publications
2
19
0
Order By: Relevance
“…Like other transcription factors, GATA-3 is a challenging therapeutic target, thus we sought to characterize its interactome by BioID. Our findings are generally consistent with the interactome previously identified in normal T cells [62], including the observation that transcriptional co-activators and corepressors, many of which are subject to recurrent gains and losses in T-cell neoplasms, respectively, were identified. However, we were most intrigued by p300, as post-translational acetylation of many GATA family members has been variously associated with regulating protein stability, protein-protein interactions, and DNA binding affinity [52,63], and previous studies further suggest a regulatory role for post-translational acetylation in regulating GATA-3 function [56].…”
Section: Discussionsupporting
confidence: 90%
“…Like other transcription factors, GATA-3 is a challenging therapeutic target, thus we sought to characterize its interactome by BioID. Our findings are generally consistent with the interactome previously identified in normal T cells [62], including the observation that transcriptional co-activators and corepressors, many of which are subject to recurrent gains and losses in T-cell neoplasms, respectively, were identified. However, we were most intrigued by p300, as post-translational acetylation of many GATA family members has been variously associated with regulating protein stability, protein-protein interactions, and DNA binding affinity [52,63], and previous studies further suggest a regulatory role for post-translational acetylation in regulating GATA-3 function [56].…”
Section: Discussionsupporting
confidence: 90%
“…Some studies suggest that ARID1A have an essential function role in the formation of lymphocytes. In animal studies, it is found that the absence of ARID1A in early lymphoid progenitor cells of mice leads to the obvious stagnation of early T cell development [ 32 ]. Our findings further indicate that the ARID1A expression is significantly linked to T helper cells.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, recent studies revealed the vital effect of ARID1A on tumor immunity. One study confirmed that ARID1A plays an important role in lymphocyte development, whereas ARID1A deletion can lead to a developmental arrest in early T cells (28). Loss of ARID1A was found to have a significant correlation with the expression of IFN-g and checkpoint genes (including PD-L1, CTLA4, and PDCD1) in microsatellite-stable colorectal cancer (29).…”
Section: Discussionmentioning
confidence: 91%